2006
DOI: 10.1603/0022-2585(2006)43[889:farpoe]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant and Repellent Properties of Essential Oils and Component Compounds Against Permethrin-Resistant <I>Pediculus humanus capitis</I> (Anoplura: Pediculidae) from Argentina

Abstract: The repeated use of permethrin and other insecticides for the control of head lice, Pediculus humanus capitis De Geer (Anoplura: Pediculidae), during past decades has resulted in the development of marked levels of resistance. Thus, new alternative insecticides are needed for the control of head lice. We studied the fumigant and repellent properties of essential oils from 16 native and exotic plants in Argentina, and 21 chemical components against permethrin-resistant head lice from Argentina. With a direct va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 16 publications
1
64
0
2
Order By: Relevance
“…These 20 have been commercially used for the production of essential oils in the pharmaceutical and cosmetic industries (Pino et al 2002). Furthermore, previous studies have shown that, in general, the toxicity of plant essential oils against insect pests is related to their major components such as 1,8-cineole (Choi et al 2006;Toloza et al 2006;Alzogaray et al 2011;Akhtar et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 20 have been commercially used for the production of essential oils in the pharmaceutical and cosmetic industries (Pino et al 2002). Furthermore, previous studies have shown that, in general, the toxicity of plant essential oils against insect pests is related to their major components such as 1,8-cineole (Choi et al 2006;Toloza et al 2006;Alzogaray et al 2011;Akhtar et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…These oils are often responsible for a plants distinctive scent or taste. Essential oils have a rather complex composition, with component compounds generally consisting of low-molecular-weight monoterpenes (10-carbon) and related phenols (Toloza et al 2006). The main characteristics of the essential oils are that they are easily extractable, ecofriendly, biodegradable, possess low or no toxicity against mammals, and are very effective against a wide spectra of insect pests (Lucia et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptol was also found in majority of other species of Eucalyptus, such as E. staigeriana (Gilles et al, 2010), E. globules (Maciel et al, 2010;Tyagi and Malik, 2011) and E. urophylla (Cheng et al, 2009). Nevertheless, the main component in other species of Eucalyptus can be a different compound, such as piperitone (E. dives), (E)-methyl cinnamate (E. olida) (Gilles et al, 2010), α-pinene (E. camaldulensis) (Cheng et al, 2009), limonene (E. staigeriana), β-citronellal (E. citriodora) (Maciel et al, 2010), or p-cymene (E. tereticorni) (Toloza et al, 2006). The chemical composition of essential oil is affected by several factors, such as species, geographical location, harvest time, plant part and isolation method (Cimanga et al, 2002;Penalver et al, 2005;Marzoug et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a wide range of molecules with repellent activities, including natural substances derived from plants as well as synthetics have been developed (Peock and Maunder, 1993) (Burgess, 1993) (Mumcuoglu et al, 1996) (Mumcuoglu et al, 2004) (Toloza et al, 2006a) (Toloza et al, 2006b) (Toloza et al, 2008) (Canyon and Speare, 2007) (Semmler et al, 2010), but nothing was known regarding their mode of action at the insect level. The results of our study indicate that PhumOR2 is linked to avoidance behavior by mediating the reception of natural repellents.…”
Section: Phumor2 As a Biological Detector Of Lice Repellentsmentioning
confidence: 99%
“…Several types of repellent products have been considered for louse control, including broad-spectrum synthetics such as N,N-diethyl-3-methylbenzamide (DEET) and plant-derived compounds such as essential oils and some of their constituents (e.g. citronellal) (Peock and Maunder, 1993) (Burgess, 1993) (Mumcuoglu et al, 1996) (Mumcuoglu et al, 2004) (Toloza et al, 2006a) (Toloza et al, 2006b) (Toloza et al, 2008) (Canyon and Speare, 2007) (Semmler et al, 2010). Nevertheless, no specific anti-louse repellent has been discovered to date (Semmler et al, 2012) (Burgess et al, 2014).…”
Section: Introductionmentioning
confidence: 99%